ANALISIS EFISIENSI TEKNIS DAN FAKTOR YANG MEMPENGARUHI EFISIENSI PADA USAHA TANI KUBIS DI DESA TALANG BELITAR KECAMATAN SINDANG DATARAN KABUPATEN REJANG LEBONG - N, Darmansyah A; Sukiyono, Ketut; Sugiarti, Sri (Jurnal AGRISEP, 2013)
As a main horticultural commodity, cabbage is cultivated by farmers for long time. Research of this commodity is mainly focused on income, productivity, production, less focused on how a technical efficiency level has been achieved by farmers. For this reason, this study is aimed at determining the level of technical efficiency and the factors that affect the level of technical efficiency of cabbage farm in the village Talang Belitar Sindang Dataran Sub District Rejang Lebong District. the method of data analysis used stochastic frontier production function assuming Cobb Douglas is the functional form of the production function area cabbage research. Fiftyfive respondents selected randomly. The results showed that the level of technical efficiency in this study the lowest high of 78.44 % and 99.74 %. The average technical efficiency of farms by 91.195 % cabbage . Production function estimation results indicate that the number of seeds, Organic Fertilizer, Urea, NPK, Pesticides and Workforce real effect on the confidence level of 99 %, while the TSP and the land area is not significant , then together the factors that influence the production of cabbage affect production by 98.7 %. While the determinant factors that affect the level of efficiency of cabbage farm showed that age of farmers and the use of technology significantly at 90 % confidence level while the farmer education, experience and trying to farm land status does not affect significantly, further found that jointly Age factor variables (age of farmers), EDU (education of farmers), EXP (experience of farmers), STA (state land) and TEK (use of technology) affect production by 61.25 % .